Poaching in context: a critical review of the role that corruption and criminal syndicates play in wildlife crime in South Africa, specifically in so far as it relates to the poaching of rhinoceros - Strydom, Tanya (2017)
Wildlife crime is a longstanding problem. People have always considered living and non-living species as resources and tradable products used for pure economic gain, which then has a negative effect on biodiversity. In addition, wildlife crime involves poachers; armed non-state actors from source nations; international crime groups; institutional corruption across global network chains and a range of players involved in demand countries, which range from organized criminal syndicates, non-state actors and legitimate authorities. States and the International community are responding to wildlife crime in the form of law enforcement and regulatory initiatives. The question therefore arises, why does wildlife crime persist and what is the driving force behind these crimes and the people involved. For example, despite the broad legislative framework, the enforcement or rather lack thereof seems to be the reason that South African rhinos are still facing destruction. This paper aims to evaluate what the relationship is between wildlife crime with rhino poaching as a focus point, corruption and organised crime. It discusses the current enforcement framework, and investigates why the enforcement framework is not supporting the legislative framework. Lastly practical and structural solutions will be discussed and evaluated